Edukasi Terapi Komplementer Isometric Handgrip Exercise Penurunan Tekanan Darah pada Penderita Hipertensi di Puskesmas Olak Kemang Kota Jambi - Kadri, Hasyim (Universitas Baiturrahim, 2026)
The problem that often occurs in hypertension sufferers is that they tend to be unstable due to lack of attention to lifestyle and irregular medication. Management of ways to prevent and treat hypertension is carried out using pharmacological and non-pharmacological treatments. Pharmacological treatment can reduce high blood pressure, but this treatment also has side effects if consumed for a long time, such as headaches, weakness, dizziness, liver dysfunction, heart palpitations and nausea. Management of hypertension or non-pharmacological treatment that is cheap and easy, can be done independently is isometric exercise is a form of static exercise that occurs when muscles contract without any visible change in muscle length or joint movement. This exercise can be done anywhere, the intensity is from light to moderate, the use of equipment is relatively cheap and the time required is relatively less, making this exercise have the potential for client compliance. Series of activities: April 5 2024 to August 5 2024, place at Olak Kemang Health Center, Jambi City for 30 participants. The results obtained by participants following PKM activities were: Activity participants were able to understand the material properly, Activity participants were able to simulate the material correctly, Activity participants were able to answer correctly questions related to material evaluation